Integrative multi-omics study identifies sex-specific molecular signatures and immune modulation in bladder cancer - Wang, Yizhou; Bhandary, Priyanka; Griffin, Kevin; Moore, Jason H.; Li, Xue; Wang, Zhiping Paul (Frontiers in Bioinformatics, 2025)
IntroductionBladder cancer shows distinct sex-related patterns, with male patients experiencing significantly higher incidence and female patients facing poorer survival outcomes. This study aimed to investigate the biological mechanisms underlying these differences using integrative multi-omics analysis.MethodsWe analyzed bladder cancer data from TCGA and GTEx, including genomic mutations, gene expression profiles, and clinical information. We performed protein-protein interaction analysis, pathway enrichment, survival analysis, and immune cell correlation.ResultsWe identified androgen receptor (AR)-related pathways as uniquely enriched in male-specific hub genes, while the Wnt signaling pathway was enriched in female-specific hub genes. In total, 14 male-specific hub genes showed significant sex-biased survival associations, including known markers—DLGAP5, SOX2, LAMA2, and COL5A2—and novel ones such as ERCC5, NID1, ANK2, and others. For females, three hub genes—RAD51C, COL22A1, and COL5A2—were identified as female-specific with survival associations. Additionally, four male-specific hub genes—DAXX, IKBKB, PDGFRA, and PPARG—were immune-related and showed sex-differential correlations with immune cell infiltration, with three of them associated with AR signaling regulation.DiscussionThese findings provide new insights into the molecular basis of sex differences in bladder cancer and could pave the way for more personalized and effective therapeutic strategies tailored to male and female patients.